Criminal Careers of Burglars and Robbers in the Netherlands - Kros, Mathijs (Journal of developmental and life-course criminology, 2023)
This paper investigates criminal career characteristics and trajectories of domestic burglars, residential and commercial robbers, and street robbers in the Netherlands. We used longitudinal data which includes the criminal cases from 1997 until 2020 for all people of 12 years or older. We studied all 89,062 offenders that had at least one criminal case in the period between 2002 and 2004. Semiparametric group trajectory models were used to cluster these offenders into groups with similar criminal careers. Our results suggest that in order to predict who will follow the career path of a life-course persistent offender, it is important to distinguish between specific groups of offenders. Life-course persistent offenders are found amongst domestic burglars, residential and commercial robbers, and street robbers, but not amongst offenders of other types of crime. Furthermore, the size of the group of life-course persistent offenders varies between the domestic burglars, residential and commercial robbers, and street robbers and is largest for domestic burglars. Other criminal career characteristics, such as age of onset, age of termination, duration, and specialisation, are also compared between offender groups.